Effect of vitamin C on salivary total antioxidant capacity in healthy male smokers - Nazanin Kamyab; Mahmood Sheikh Fathollahi; Azadeh Khaleghi; Zohreh Mordouei (Tehran University of Medical Sciences, 2019)
Background and Aims: Saliva is the first body fluid that is exposed to the free radicals found in cigarette smoke. Antioxidant substances in saliva, such as vitamin C, play an important role in the defense mechanism against free radicals. Therefore, the aim of this study was to examine the effect of vitamin C on the total antioxidant capacity of saliva in smokers. Materials and Methods: This randomized clinical trial was performed on 60 healthy male smokers who referred to the dental clinic in Rafsanjan in 2017. Individuals were randomly divided into three groups. The first and second groups received 500 and 1000 mg of vitamin C boiling tablets for three weeks. The third group did not receive any vitamin C supplements. The total antioxidant capacity of saliva was measured using an antioxidant kit and an ELISA reader. Data were analyzed using paired t-test, one-way ANOVA, and Duncan's multiple comparisons test. Results: The results showed that the mean total antioxidant capacity of saliva after the intervention was found statistically significant among groups (P<0.001). However, the mean total antioxidant capacity of saliva did not differ in the groups receiving 500 and 1000 mg of vitamin C (P=0.420). Conclusion: The results showed that taking vitamin C increased the total antioxidant capacity of saliva in smokers.